2021
DOI: 10.1021/jacs.1c10845
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Uses of the Reaction of Frustrated Lewis Pair (FLP) with Hydrogen

Abstract: The articulation of the notion of “frustrated Lewis pairs” (FLPs) emerged from the discovery that H2 can be reversibly activated by combinations of sterically encumbered main group Lewis acids and bases. This has prompted numerous studies focused on various perturbations of the Lewis acid/base combinations and the applications to organic reductions. This Perspective focuses on the new directions and developments that are emerging from this FLP chemistry involving hydrogen. Three areas are discussed including n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 165 publications
0
101
0
2
Order By: Relevance
“…3 Frustrated Lewis pairs (FLPs) are ubiquitous as metal-free catalysts for a myriad of chemical transformations. [4][5][6][7] The frustration induced by sterically hindered Lewis acid (LA) and base (LB) centres permits cooperative action of, and catalysis with, a multitude of substrates including carbon dioxide, dihydrogen and cyclic ethers. [8][9][10][11][12][13][14][15] In 2017, our group demonstrated that FLP reactivity is maintained when incorporated into a polymeric system, revealing a new class of stimuli-responsive materials that exploit FLP-mediated small molecule activation.…”
Section: Introductionmentioning
confidence: 99%
“…3 Frustrated Lewis pairs (FLPs) are ubiquitous as metal-free catalysts for a myriad of chemical transformations. [4][5][6][7] The frustration induced by sterically hindered Lewis acid (LA) and base (LB) centres permits cooperative action of, and catalysis with, a multitude of substrates including carbon dioxide, dihydrogen and cyclic ethers. [8][9][10][11][12][13][14][15] In 2017, our group demonstrated that FLP reactivity is maintained when incorporated into a polymeric system, revealing a new class of stimuli-responsive materials that exploit FLP-mediated small molecule activation.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to take into consideration that amines weakly coordinate to the surface of the metallic nanoparticles as shown experimentally and theoretically in previous works [31,46], and for that reason are in equilibrium with the solution. Amines and phosphines have been described to form frustrated Lewis pairs (FLP) [40] with the acidic metallic surfaces of gold [38] and nickel-copper [39] for instance, and are able to activate H 2 or Si-H bonds effectively into those surfaces. We cannot discard that this phenomenon is also occurring in our catalytic media as amines are in excess with respect to the ruthenium atoms, thus FLP interactions could help to accelerate the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Even so, it has been demonstrated in some works that organic ligands are able to change the outcome of catalysed reactions when compared to bare metallic surfaces, or increasing activity or favouring the synthesis of a selected product [31,[35][36][37]. Interesting enough, recently some works point out that basic ligands together with acidic metallic surfaces could form frustrated Lewis pairs (FLP), which will be responsible for the modulation of the reactivity of metallic surfaces [38][39][40]. This phenomenon, not yet fully studied, adds complexity to the understanding of the role of ligands in heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Against this background, we have focused on main-group catalysis 19,20 including the use of frustrated Lewis pairs (FLPs) that are comprised of Lewis bases (LBs) and triaryl boranes as the Lewis acids (LAs). [21][22][23] Triaryl boranes of the type B n such as B(C6F5)3 (B 1 ) have been reported to catalyze the hydrogenation of N-heteroaromatic compounds such as 2-methylquinoline (Qin) under diluted conditions. [24][25][26] FLPs are well known to mediate the heterolytic cleavage of the H−H bond to generate [LB−H][H−LA] species (Fig.…”
Section: Main Textmentioning
confidence: 99%